Word extraction - Siti Munirah, Abdul Kudus (2009)
In content-based image processing system, describing and extracting word is a key question. This project is an approach to extracting word characters from images using image processing technique of MATLAB software, which in this system developed contain two phases. Those phases are preprocessing phase, where system used binarization and smoothing technique, while in second phase which is feature extraction phase, system used morphological technique. The word extraction eliminates noise and the distortions on the same document to remain the important characters. The result generated by this system is 87.5% satisfactory with the ability to read the valueable words and documents. Thus, the system and method is effective and feasible.